KOHESI GRAMATIKAL DALAM PROSA TORAJA (Grammatical Cohesion in Torajanese Prose) - Abd. Rasyid (Balai Bahasa Sulawesi Selatan, 2015)
This paper aims at describing grammatical cohesion in Torajanese prose focused on the analysis included references and substitutions. Results of this study are expected to be useful theoretically and practically. Theoretically, the results of this study are expected to strengthen and give more specific information, detail, and depth about cohesion in Torajanese language. In practical terms, the results of this study are expected to be useful for the development and and teachin literature that is considered relevant. In this paper qualitative descriptive method is used to describe or analyze the data of how grammatical cohesion in Torajanese prose is. Data collection techniques include reading, recording, and selecting. Result of analysis finds out that cohesion tool used is reference ta ‘that’, iatu ‘that’, and iate ‘this’, as well as substitution is ia ‘she/he/it’, iko ‘you’, -na ‘her/his/it’, and inde ‘here .